2014
DOI: 10.5137/1019-5149.jtn.9517-13.0
|View full text |Cite
|
Sign up to set email alerts
|

Combining pyramidal tract mapping, microscopic-based neuronavigation, and intraoperative magnetic resonance imaging improves outcome of epilepsy foci resection in the sensorimotor cortex

Abstract: AIM:To explore the clinical value of combining pyramidal tract mapping, microscopic-based neuronavigation, and intraoperative magnetic resonance imaging (iMRI) in the surgical treatment of epileptic foci involving sensorimotor cortex. MATERIAL and METHODS:We retrospectively analyzed 69 patients with focal epilepsy involving motor and sensory cortex. The surgical operations in Group I (n=38) were performed under the guidance of conventional neuronavigation, and the operations of Group II (n=31) were aided by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…A satisfactory seizure outcome (Engel class I and II) was found in 90.36% of patients who underwent surgery with neuronavigation. Including the results described by Cui et al, the rate of good seizure outcome was 82.37% [14].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A satisfactory seizure outcome (Engel class I and II) was found in 90.36% of patients who underwent surgery with neuronavigation. Including the results described by Cui et al, the rate of good seizure outcome was 82.37% [14].…”
Section: Discussionmentioning
confidence: 80%
“…However, a detailed analysis of these studies shows that some authors have the tendency to describe all their series of good results only. More realistically, Cui et al observed that among 69 patients with focal epilepsy treated by surgery with neuronavigation, 62.31% had a good outcome (Engel I and II) [14]. Meanwhile, five studies excluded from this specific analysis described postoperative status as ''free of seizures'', ''partial control'' or ''without control'', and thus not allowing an accurate measurement of postoperative outcomes [15][16][17][18][19].…”
Section: Postoperative Seizure Controlmentioning
confidence: 99%
“…To counter this, iMRI has been successfully integrated with these imaging techniques in lesional epilepsy surgery. 7,32 In addition to traditional intraoperative CT and MRI, further technologies such as advanced intraoperative ultrasonography and intraoperative elasticity imaging may better aid in real-time identification of dysplastic lesions and in more accurate depiction of margins. 5,18 Furthermore, intraoperative ultrasonography has been shown to successfully integrate with functional MRI and DTI to provide an intraoperative update to neuronavigation accounting for brain shift.…”
Section: Discussionmentioning
confidence: 99%
“…При необходимости хирург имеет возможность переключать операционный микроскоп между реальным и виртуальным изображением либо совмещать первое и второе. Навигационная система состоит из станции планирования, ИК и электромагнитной антенны, различных навигируемых хирургических инструментов [11][12][13].…”
Section: нейронавигацияunclassified